TRANSMISSION OF ALFALFA MOSAIC VIRUS THROUGH SUBCOCCINELLA VIGINTIQUATUORPUNCTATA (L.) (COLEOPTERA: COCCINELLIDAE) IN ALFALFA GROWING AREAS IN TÜRKİYE - AYDEMIR BARIS; Ali FERHAN MORCA; Mustafa ALKAN (Journal of Animal and Plant Sciences, 2024)
Alfalfa Medicago sativa L. (Fabaceae: Leguminosae) is an important fodder crop due to its highly nutritious animal feed and potential to adapt various environmental conditions. The average alfalfa yield in Türkiye is considerably higher than the world's average. Several diseases and pests exert negative impacts on alfalfa yield. This study investigated the status of the alfalfa mosaic virus (AMV) and the presence of insect species that could be new vectors for AMV in the alfalfa growing areas of Zonguldak and Bartın provinces in Türkiye. AMV is non-persistently transmitted by aphid species, but it is also known to be transmitted by pollen and seeds. The most prevalent harmful insect species in the studied area were Subcoccinella vigintiquatuorpunctata (L.) (Coleoptera: Coccinellidae), and Gonioctena fornicata (Brüggeman) (Coleoptera: Chrysomelidae). The AMV was prevalent in the tested plants at a rate of 85.00%, with infection rates of 80.55% in mature larvae of S. vigintiquatuorpunctate, 80.00% in pupae, and 96.77% in adults. When looking at the relationship of AMV with common pest species, AMV was not detected in all life stages of G. fornicata. In contrast, AMV was detected in all life stages of S. vigintiquatuorpunctata except eggs. This study is the first in the world to detect the presence of AMV in S. vigintiquatuorpunctata. However, further studies are needed to determine whether S. vigintiquatuorpunctata transmits AMV persistently, semi-persistently, or non-persistently.
Keywords: Forage crops; 24-spot ladybird; Molecular detection; Insect Vector; Prevalence